The Effect of Processing on Nutrient Utilization of Pigeonpea (Cajanus cajan) Seed Meal and Pigeonpea Seed Meal Based Diets by Pullets - Amaefule, K.U.; Nwagbara, N.N. (International Journal of Poultry Science, 2004)
Two experiments were conducted with fifty-four 9-week old Bovan Nera pullets (24 in experiment 1 and 30 in experiment 2) to determine the effect of processing on the nutrient utilization of pigeonpea seed meal (PSM) and PSM-based diets by pullets. The seeds were processed either as boiled, toasted, soaked or raw (unprocessed). In experiment 2, raw or processed PSM were each included as 10% of a maize-soybean diet. Parameters considered were DM, CP, CF and ether extract utilization of the PSM and that of PSM-based diets. Results showed that in experiment 1, processing significantly increased (P<0.05) CP retention of the pullets while boiled and raw PSM had significantly higher (P<0.05) CF utilization than toasted and soaked. In experiment 2, boiled PSM diet significantly improved (P<0.05) CP retention of the pullets, while soaked PSM diet significantly reduced both CP retention and CF utilization of the pullets. It was concluded that processing of pigeonpea seeds for use in pullet diets would improve CP retention and other nutrient utilization especially boiling and toasting.